ChemInform Abstract: Unusual Reactivity of Nitronates with an Aryl Alkyl Carbonate: Synthesis of α‐Amino Esters. Issue 17 (April 2015) - Reddy, Golipalli Ramana; Mukherjee, Debopreeti; Chittoory, Arjun Kumar; Rajaram, Sridhar
Abstract The presented method offers a safe and scalable alternative to the well‐known Strecker reaction.